Seeing the world through the eyes of cultured cells - Tan, Joycelyn; Kunzmann, Guy B.; Virtue, Sam; Cantor, Jason R.; Fazakerley, Daniel J. (Cell metabolism, 2025)
The metabolic environment experienced by cultured cells often differs from physiological conditions. Here, we highlight the effects that the microenvironment can have on cultured cell behavior and advocate for researchers to re-evaluate culture practices to enhance the relevance and translational potential of in vitro studies. [Display omitted] The metabolic environment experienced by cultured cells often differs from physiological conditions. Here, we highlight the effects that the microenvironment can have on cultured cell behavior and advocate for researchers to re-evaluate culture practices to enhance the relevance and translational potential of in vitro studies.